2017
DOI: 10.1007/s00125-017-4465-2
|View full text |Cite
|
Sign up to set email alerts
|

The association between Helicobacter pylori seropositivity and risk of new-onset diabetes: a prospective cohort study

Abstract: Aims/hypothesis Previous studies have suggested a possible connection between Helicobacter pylori (H. pylori) infection and diabetes risk. However, prospective studies examining direct associations between these two factors are relatively lacking. In this prospective cohort study, we aimed to evaluate the association between H. pylori infection and risk of developing diabetes. Methods We performed a population-based prospective study, recruiting participants aged 45-74 years and without diabetes from the Chine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
1
11
0
1
Order By: Relevance
“…So far, although a number of studies have examined an association between H. pylori infection and diabetes, the results were conflicting. Part of the reason for the conflicting results could be due to small sample size and inappropriate adjustment of risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, although a number of studies have examined an association between H. pylori infection and diabetes, the results were conflicting. Part of the reason for the conflicting results could be due to small sample size and inappropriate adjustment of risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of studies have examined the association between H. pylori and diabetes, the results were conflicting. Furthermore, if there is a link between H. pylori infection and diabetes, it is natural to expect a change in diabetes state after eradication.…”
Section: Introductionmentioning
confidence: 99%
“…Kayar et al showed a significant relationship between HP infection and MetS, insulin resistance, inflammation, and diabetic complications[9]. Recently, seropositivity of HP infection was reported to be associated with lower risk of DM[16]. However, the concentrations of antibodies against CagA, a major factor in HP infection, might be elevated in patients who had a negative HP serological test[11].…”
Section: Discussionmentioning
confidence: 99%
“…Частота Нр при наличии коморбидного СД выше, чем при ЯЖ и ЯК без такой эндокринной патологии [17,18]. Серопозитивность больных СД по Нр составляет около 60 % [19], а носительство инфекции регистрируется на 90 % чаще, чем в общей популяции, что прямо коррелирует с уровнями в крови фактора некроза опухоли α, маннозосвязанного лектина и липопротеинов низкой плотности. С хеликобактерной инфекцией у таких больных тесно связаны генотипы rs1800450 AA и rs1800620 [20].…”
Section: патологія верхніх відділів травного каналу / Pathology Of Upunclassified